2001
DOI: 10.1165/ajrcmb.24.4.4249
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-9 Reduces Lung Fibrosis and Type 2 Immune Polarization Induced by Silica Particles in a Murine Model

Abstract: We examined the effect of interleukin (IL)-9, a cytokine active on B and T lymphocytes and associated with bronchial asthma, on the development of lung fibrosis induced by crystalline silica particles. Therefore, we compared the response to silica (1 and 5 mg/animal, intratracheally) in transgenic mice that constitutively express high levels of IL-9 (Tg5) and their wild-type counterparts (FVB). At 2 and 4 mo after treatment with silica, histologic examination and measurement of lung hydroxyproline content show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
2
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 37 publications
4
99
2
3
Order By: Relevance
“…In accordance with these observations, reports have shown increased IL-4 expression in bleomycin (blm)-, 3 silica-, and radiation-induced lung injury and suggested that activated macrophages represent the major source of IL-4 during the establishment of active lung fibrosis (17)(18)(19). In human studies, the progression of idiopathic pulmonary fibrosis is also associated with a sustained IL-4 production (20,21).…”
mentioning
confidence: 63%
“…In accordance with these observations, reports have shown increased IL-4 expression in bleomycin (blm)-, 3 silica-, and radiation-induced lung injury and suggested that activated macrophages represent the major source of IL-4 during the establishment of active lung fibrosis (17)(18)(19). In human studies, the progression of idiopathic pulmonary fibrosis is also associated with a sustained IL-4 production (20,21).…”
mentioning
confidence: 63%
“…This protective effect, also observed with IL-4, was associated with a strong reduction of serum levels of TNF-␣, IL-12/p40, and IFN-␥ induced by the bacteria or LPS injection, and with a dramatic increase of IL-10. Secondly, in a silica-induced lung fibrosis model, IL-9 had a beneficial antifibrotic effect associated with an inhibition of the silica-induced up-regulation of IL-4 expression (14). Interestingly, in a rat model of lung fibrosis induced by irradiation, IL-4 has been shown to be mostly produced by alveolar macrophages (15).…”
Section: Il-9 Inhibits Oxidative Burst and Tnf-␣ Release In Lipopolysmentioning
confidence: 98%
“…ODN contained Ͻ0.1 units of endotoxin/mg, as assessed by a Limulus amebocyte cell lysate assay. Silica particles were obtained from U.S. Silica and were sterilized at 200°C for 2 h to inactivate any contaminating endotoxin (25).…”
Section: Odns and Reagentsmentioning
confidence: 99%